Error Analysis on EFL Learners’ Analytical Exposition Writing - Aprilista Dwi Permatasari; Testiana Deni Wijayatiningsih; Dodi Mulyadi (Surakarta English and Literature Journal, 2018)
This research was aimed to find out the errors that occur in writing analytical exposition text which are made by students in XI grade of SMA N 15 Semarang. The data were taken from the students' writing product. All data concerning grammatical errors were analyzed by using Ellis' theory. This research used descriptive qualitative method. The results of this research showed that there were three kinds of errors made by the students. First, omission is leaving out an item that is required for an utterance to be considered grammatically. Second, misinformation is using one grammatical form in place of another grammatical form. Lastly, misordering is putting the words in an utterance in the wrong order. This research was expected to give understanding about grammatical errors in writing analytical exposition text so it can help students in writing English text well.